Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/ece3.346
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resistance to multiple pathogen species: anther smuts of Silene uniflora

Abstract: The occurrence of multiple pathogen species on a shared host species is unexpected when they exploit the same micro-niche within the host individual. One explanation for such observations is the presence of pathogen-specific resistances segregating within the host population into sites that are differentially occupied by the competing pathogens. This study used experimental inoculations to test whether specific resistances may contribute to the maintenance of two species of anther-smut fungi, Microbotryum sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 60 publications
(114 reference statements)
0
39
0
Order By: Relevance
“…Plants can have highly specific defenses that could lead to apparent competition, effective against only one of two closely related pathogens (Chung et al 2012). Recent studies have demonstrated patterns of exclusion of new infections by existing viral infections, even when time of inoculation between the two variants was as short as 6 h (e.g., Julve et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Plants can have highly specific defenses that could lead to apparent competition, effective against only one of two closely related pathogens (Chung et al 2012). Recent studies have demonstrated patterns of exclusion of new infections by existing viral infections, even when time of inoculation between the two variants was as short as 6 h (e.g., Julve et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A sampling site was defined as a location in which samples were collected a few metres apart. Sampling was performed by numerous investigators throughout Europe and was carried out as part of general disease surveys, other field trips, or as part of more formal investigations (Chung et al., ; Le Gac, Hood, Fournier et al., ; J. Abbate & J. Antonovics, unpublished studies). Within sampling sites, a single diseased flower was collected per individual plant, stored in silica gel, and DNA from the diploid teliospores was extracted for genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation for coexistence of these three fungal species could be that they are allopatric, although they have been found to co‐occur in the same sites (Abbate & Antonovics, ; Chung, Petit, Antonovics, Pedersen, & Hood, ; Le Gac, Hood, Fournier et al., ); however, sampling has been limited thus far, and it remains possible that contact zones of allopatric distributions were sampled. An alternative hypothesis is that the species display differential specialization towards S. vulgaris versus S. uniflora .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrahost competitive exclusion may also be important and is well documented among Microbotryum strains, including within‐ and among‐species interactions (Fortuna et al, ; Gold et al, ; Hood, ). Studies have indicated heritable variation in anther‐smut disease resistance (Alexander & Maltby, ; Cafuir, Antonovics, & Hood, ; Carlsson‐Granér & Pettersson, ; Chung, Petit, Antonovics, Pedersen, & Hood, ), but the mechanisms of resistance and whether it is inducible have not been determined.…”
Section: Discussionmentioning
confidence: 99%